NUMERICAL MODELING OF HARDENING OF UNINTERRUPTEDLY-CASTED BRONZE CASTING - E. I. Marukovich (Litʹë i Metallurgiâ, 2009)
The three-dimensional numerical model for calculation of thermal fields during solidification of continuously casted bronze casting is developed. Coefficients of heat transfer on borders of calculation areas on the basis of the solution of inverse heat transfer conduction problem are determined. The analysis of thermal fields, depending on loop variables of drawing and the sizes of not cooled zone of crystallizer is curried out.